The Challenge of Misleading Information: Does the Interaction between Zinc and Vitamin D Influence the Immune Response against SARS-CoV-2 in the Elderly Population? - Deise Maria Rego Rodrigues Silva; Pedro Henrique Macedo Moura; Rajiv Gandhi Gopalsamy; Eloia Emanuelly Dias Silva; Marina dos Santos Barreto; Ronaldy Santana Santos; Pamela Chaves de Jesus; Jessiane Bispo de Souza; Lucas Alves da Mota Santana; Adriana Gibara Guimarães; Lysandro Pinto Borges (Life)
Immunization is a challenge for the elderly population and can leave this group more vulnerable to opportunistic pathogens such as SARS-CoV-2. Due to this situation, while vaccines were in the development phase, hypotheses were raised about the role of vitamins and minerals in immunization. In Brazil, there was a controversy regarding the well-known COVID-19 Kit, a standardized prescription for positive cases that contained zinc, and vitamin D, and anti-parasitic drugs. There was great controversy in scientific circles, since COVID-19 brought a major challenge for health professionals and public authorities: misleading information. In this study, we evaluated the role of vitamin D and zinc in the production of anti-SARS-CoV-2 neutralizing antibodies (NAbs) in a group of elderly residents in a nursing home in northeastern Brazil. Serum levels of COVID-19 NAbs were assessed, along with vitamin D and zinc, in two phases. The first (T1) was in August 2022 with 26 elderly people, and the second (T2) was in March 2023 with 21, due to the death of five participants. Overall, we observed satisfactory levels for vitamin D, with no participants showing a deficiency in either test, and zinc, with only two participants having a negative result at T1 and three at T2. However, a drop in the average number of NAbs was observed, especially in women (T1 = 89 ± 19 vs. T2 = 57 ± 44), highlighting the importance of monitoring this immunological parameter in the population studied. Based on the results, we suggest that there is no synergism between the micronutrients studied and NAbs (p > 0.05). Further studies are needed to consolidate the findings of an absence of synergism between vitamin D and zinc in the maintenance of NAbs.